Estudio de las fuerzas de arrastre de cables umbilicales de robots de inspección o desobstrucción de tuberías - Marenco, Javier (2017)
The present work makes a study of the drag forces of umbilical cables of pipes inspection robots and aims to determine a valid model for their calculation. For this purpose, the physical models are developed in relation to the friction forces for the straight and curved sections in all their possible configurations, obtaining for each case a differential equation that models the friction phenomenon and that includes fluid and cable the characteristics. By solving the differential equation, an explicit expression is obtained for the value of the frictional force in each case. In the present work, the obtained model is evaluated in comparison with the traditional simplified model. It is also presented a study about the influence of the stiffness of the cable and how this characteristic generates the forces of the normal general forces at the ends of the curves that, finally, result in an additional component of the frictional forces. By comparison with actual drag force measurements, the model obtained is validated. The complexity of the calculations required for the determination of the pull forces in real pipes makes it necessary to use software tools to facilitate it. For this reason, two software applications are developed, one specific for rigid pipes and another one for flexible pipes. A series of strategies of how to keep low the maximum value of the cable tension are presented too.